IMPROVEMENT OF CYCLONE INSTALLATION - Tukhtabaev S.T.; Gapparova M. A. (Web of Journals Publishing, 2025)
Cyclones for cleaning dusty air flow are one of the main equipment for cleaning air from small impurities, fibrous waste, they are widely used in cotton and textile enterprises.
Keywords: Small impurities, fibrous waste, storage bin, cotton drying and cleaning, scutching and carding production, spinning, weaving production, dust, air flow.